A study on evaluation of the performance of urban bus in Kuantan Pahang - Nor Zubaidah, Mohamad (2014)
Public transportation such as urban bus is one of the utilities that are often used by people across Malaysia. Public transport must comply with several indicators such as bus utilization, passenger ridership, load factor, cycle times, time headways etc. Due to the rapid pace of development, high employment demand and meet the basic needs of the urban area, the performance of public transport should be addressed. Therefore, the objective of the study is to evaluate the operating performance of urban bus services and to identify the drawbacks and propose improvement. This study is conducted based on the observation of the performance of Rapid Kuantan which is the main of public transport in Kuantan. Data collection is achieved by observing at the bus terminal (bus stop) and onboard the buses by doing passenger counting. Result the observation showed, the average travel distance is higher because the value is higher than the World Bank Standard (230-260km) and its means good because the buses are highly utilized. On the other hand, for the headway, is still exceeds the World Bank Standard. Therefore the addition a number of bus can reduce the headway.For cycle times, routes for Hentian Bandar - Pekan and Hentian Bandar - Bukit Sagu is exceeds the World Bank Standard, which is (244minutes and 142minutes). In these cases, it would be better if bus operations to reduce the waiting time of passengers until the passengers on the bus are full. Lastly, the load factor for Hentian Bandar-Bukit Sagu is exceeds to 70% which is (85.8% and maximum number pax is 80%).This shows the area of the bus service is very encouraging.